2015
DOI: 10.4187/respcare.04199
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Long-Term CPAP Treatment on Sleep Quality and Blood Pressure in Adherent Subjects With Obstructive Sleep Apnea

Abstract: BACKGROUND: Obstructive sleep apnea (OSA) is associated with increased risk of cardiovascular diseases. Although CPAP is the first treatment choice for moderate-to-severe OSA, acceptance of and adherence to CPAP remain problematic. High CPAP adherence is generally defined as >4 h of use/night for >70% of the nights monitored. We investigated the long-term beneficial effects of CPAP on sleep quality and blood pressure in subjects with moderate-to-severe OSA according to high or low CPAP adherence. METHODS: We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
(45 reference statements)
0
18
0
Order By: Relevance
“…34,35 Despite the relationship between obstructive sleep apnea and headache intensity, 11 only approximately one-third of respondents with self-reported sleep apnea had used a CPAP device in the 90 days before assessment. The acceptance of and adherence to CPAP treatment is problematic; 36 for example, the treatment has the potential to interfere in intimate relationships between couples. 37 As such, low overall adherence rates to CPAP treatment similar to those observed in our study have been reported, [36][37][38] leading to the suggestion that cognitive behavioral training and peer group support be implemented alongside CPAP treatment to improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Despite the relationship between obstructive sleep apnea and headache intensity, 11 only approximately one-third of respondents with self-reported sleep apnea had used a CPAP device in the 90 days before assessment. The acceptance of and adherence to CPAP treatment is problematic; 36 for example, the treatment has the potential to interfere in intimate relationships between couples. 37 As such, low overall adherence rates to CPAP treatment similar to those observed in our study have been reported, [36][37][38] leading to the suggestion that cognitive behavioral training and peer group support be implemented alongside CPAP treatment to improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, younger patients showed the highest non-compliance rates when having a recurrent ACS compared to patients without any previous history of ACS. A better understanding of the predictors of CPAP compliance is interesting because adherence to CPAP treatment is essential to achieving the beneficial effects of CPAP (23,24). Therefore, knowing the predictors of non-compliance may help in the development of clinical practice strategies directed towards improving adherence to treatment in groups with a high risk of poor compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to CPAP treatment is still a critical and complex issue, subjected to the influence of a wide array of factors[75-79]. Poor adherence to CPAP is generally acknowledged as a major limiting factor in treating OSAS, with a negative impact on therapeutic success[80-82]. Studies conducted in the 1990s or even recently, revealed that approximately 30%-50% of OSAS patients rejected CPAP immediately, the proportion of noncompliant patients reaching 80% within a year[83-86].…”
Section: Circulating Stem/progenitor Cellsmentioning
confidence: 99%